Dietary Patterns and Changes in Weight Status Among Chinese Men and Women During the COVID-19 Pandemic - Xu, Xiaoyue; Yan, Alice F.; Wang, Youfa; Shi, Zumin (Frontiers in Public Health, 2021)
Aims: To identify dietary patterns during the COVID-19 pandemic and to examine their association with changes in weight status in the Chinese population. Method: The 2020 China COVID-19 cross-sectional survey is an anonymous 74-item survey administered via social media across 31 provinces in mainland China between April and May 2020. Dietary data were assessed by a Food Frequency Questionnaire and changes in weight status were self-reported. Exploratory factor analysis using the principal component analysis method was applied to identify dietary patterns. Multinomial regression models were conducted, and forest plots were used to present the associations between dietary patterns and changes in weight status. Results: Of a total of 10,545 adults (aged ≥18 years), more than half of participants reported to have weight gain, with 18.6% of men and 16.3% of women having weight gain greater than 2.5kg. Approximately 8% of participants reported to have weight loss, with 2.1% of men and 2.5% women having weight loss greater than 2.5kg. Two dietary patterns, namely the modern and prudent dietary patterns, were identified during the COVID-19 pandemic. The modern dietary pattern was loaded heavily with soft drinks, fried foods, pickles, and inversely with fresh vegetables. The prudent dietary pattern was characterized by high intake of fresh fruits, vegetables, and inversely with soft drinks and fried food. The modern dietary pattern was positively associated with weight gain in men and women, while the prudent dietary pattern was negatively associated with both weight gain and loss in men and women during the COVID-19 pandemic. Conclusion: Dietary patterns during COVID-19 are significantly associated with changes in weight status, which may subsequently increase the risk of diet-related non-communicable disease among the Chinese population.